Hegel on Byzantium and the Question of Hegelian Neoplatonism - Arabatzis, Georges (Peitho. Examina Antiqua, 2014)
The article examines how Hegel’s negative view of Byzantium is different from the Enlightenment’s critique and especially from Voltaire’s criticism of medieval history. In order to account for the Hegelian specificity of interpretation an effort is made to translate the chapter on Byzantium from the Philosophy of History in terms of the analysis of the Phenomenology of the Spirit and, more precisely, on the basis of the chapters on sensible certitude and on the domination and servitude. Considering that for Hegel every philosophical school possesses an autonomous value, one has to wonder why the Byzantine moment of the Spirit is destined to stagnation. The question about Hegel’s Neoplatonism, especially his affiliation with Proclus’s system, shows how the distance separating the Hegelian system from the Proclusian one explains the inadequacy of the latter as to drawing the consequences from the Byzantine spiritual stagnation.